Prevalence of anaemia among the hospitalized children in a rural tertiary care teaching hospital - Muthusamy, Bala Gopal; Venugopal, Vinayagamoorthy; S., Sumithra (International Journal of Contemporary Pediatrics, 2017)
Background: The most important nutritional deficiency (micronutrient deficiency) among children in the present world is iron deficiency. The objective of this study was to evaluate the prevalence of nutritional anemia (iron deficiency anemia) among the hospitalized children in the tertiary care rural hospital. To evaluate the distribution of anemia among various age groups, sex and its association with various systemic illness. Methods: Retrospective (record based) cross sectional study carried out in a tertiary care teaching hospital. Information regarding age, gender, chief complaints, laboratory investigations carried out like total WBC count, haemoglobin was collected. Final diagnosis with system of involvement was documented. These factors were analysed. Results: Data collected from 905 patients were analysed for the study purpose. Out of 270 children in the age group of less than 2 years 72% of children were anemic. In the age group of 2-5 years55.7% of children were anemic. Nearly 2/3 of children in less than 5 years of hospitalized children were anemic. Overall 50% of children between1 month to 12 years were anemic. System wise analysis have shown 57% of respiratory cases, 47 % of gastrointestinal cases and 48% of infectious disease cases were anaemic. Conclusions: Nutritonal anemia is a major health burden in young children in developing countries. Iron deficiency in early life during the period of brain maturation is extensively studied by various research groups. Changes in brain were also reported in animal studies. Understanding the impacts of iron deficiency in terms of its role in cognitive development, intellectual development, motor development, immune function, school performance and physical development this is considered as an important and urgent public health problem in our country.